2013
DOI: 10.1016/j.buildenv.2013.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Urban form and function as building performance parameters

Abstract: The climate in cities differs significantly from those found in the surrounding area. These differences results from modifications of the Earth's surface that alters the disposition of "natural energy balance" at a micro-scale and the concentration of activities that results in anthropogenic emissions that change the composition of the atmosphere. These urban effects have distinctive temporal and spatial properties with different impacts on building energy performance depending on their purpose, which are rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 20 publications
(20 reference statements)
0
31
0
1
Order By: Relevance
“…Although this supports the conclusion that SCEN and ECEN have a positive relationship with UPA, it suggests that classifying the samples by considering their SCEN and ECEN level would be worthful. Clue 3: according to the experience from cities in developed countries, usually there is a division of functions among cities (Futcher et al, 2013); some have a function of production, whereas others, for livelihood and social services, such as entertainment and hospitals (Puissant and Lacour, 2011). Although the division of functions for different cities was not clear in China, it is worth considering such a distinction as a way of classifying them.…”
Section: Clues For Clustering Analysis With Panel Datamentioning
confidence: 99%
“…Although this supports the conclusion that SCEN and ECEN have a positive relationship with UPA, it suggests that classifying the samples by considering their SCEN and ECEN level would be worthful. Clue 3: according to the experience from cities in developed countries, usually there is a division of functions among cities (Futcher et al, 2013); some have a function of production, whereas others, for livelihood and social services, such as entertainment and hospitals (Puissant and Lacour, 2011). Although the division of functions for different cities was not clear in China, it is worth considering such a distinction as a way of classifying them.…”
Section: Clues For Clustering Analysis With Panel Datamentioning
confidence: 99%
“…Furthermore the effects of the urban heat island are frequently also ignored. This can have a dramatic impact on the timing and magnitude of energy use within buildings [156].…”
Section: Discussionmentioning
confidence: 99%
“…for every 1°C rise ambient temperature rise, the electricity consumption in Hong Kong was estimated to increase by 9.2%, 3.0%, and 2.4% in domestic, commercial and industrial sectors, respectively - Fung et al, 2006) a recent study in Malaysia found that every 1°C increment in outdoor temperature will cause a 2% drop in the coefficient of performance of split-type air conditioners (Yau and Pean, 2014). This is in sharp contrast to heating in urban areas, where, wasted heat tends to reduce the heating load for surrounding buildings (Futcher et al, 2013). The current increase in temperature due to air conditioner use was estimated to be 0.5°C but could be up to 2°C if the air conditioner use is to double (de Munck et al, 2013: 210).…”
Section: Uniqueness Of Cooling Loadmentioning
confidence: 99%